2010
DOI: 10.2486/indhealth.ms1128
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Multiwall Carbon Nanotubes for an Intratracheal Instillation Study with Rats

Abstract: Much concern has been raised over the health consequences of workers exposed to carbon nanotubes. In order to characterize multi-wall carbon nanotubes (MWCNT) suspended in a phosphate-buffered saline containing 0.1% Tween 80 for an intratracheal instillation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
(32 reference statements)
3
23
0
Order By: Relevance
“…Persistence of MWCNT fibers in the alveolar interstitium might allow sufficient time for migration of the fibers through the pulmonary lymphatic pathway adjacent to the pleural cavity. Deposition of MWCNT in the pulmonary lymphatics such as BALT suggests that the dispersed MWCNT fibers might migrate from the alveolar interstitium to the pleura and exert asbestoslike lung pathogenicity in the pleural cavity, as hypothesized by Poland et al 7) The mean length and width of MWCNT fibers used in the present study were 5.0 m m and 88 nm, respectively, with an averaged aspect ratio of 57, and fibers longer than 5 m m were found to occupy 38.9% of total fibers 22) , suggesting a similarity in size and shape of MWCNT and asbestos fibers. Peritoneal and intrascrotal administrations of MWCNT fibers having an equal length and width as those used in the present study are reported to have induced peritoneal mesotheliomas in male p53 gene-deficient mice 5) and intact male F344 rats 6) , respectively.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Persistence of MWCNT fibers in the alveolar interstitium might allow sufficient time for migration of the fibers through the pulmonary lymphatic pathway adjacent to the pleural cavity. Deposition of MWCNT in the pulmonary lymphatics such as BALT suggests that the dispersed MWCNT fibers might migrate from the alveolar interstitium to the pleura and exert asbestoslike lung pathogenicity in the pleural cavity, as hypothesized by Poland et al 7) The mean length and width of MWCNT fibers used in the present study were 5.0 m m and 88 nm, respectively, with an averaged aspect ratio of 57, and fibers longer than 5 m m were found to occupy 38.9% of total fibers 22) , suggesting a similarity in size and shape of MWCNT and asbestos fibers. Peritoneal and intrascrotal administrations of MWCNT fibers having an equal length and width as those used in the present study are reported to have induced peritoneal mesotheliomas in male p53 gene-deficient mice 5) and intact male F344 rats 6) , respectively.…”
Section: Discussionsupporting
confidence: 71%
“…In the separate paper 22) , we reported that the 20-min and additional 30-s ultrasonication and intratracheal instillation of MWCNT suspended in PBS containing 0.1% Tween 80 allowed good dispersion of MWCNT fibers in the suspension at the time of intratracheal instillation with a microspray cannula. Besides, the well-dispersed MWCNT fibers were partly engulfed by alveolar macrophages in the alveolar area of MWCNTdosed rats sacrificed on Day 1 after instillation, suggesting the occurrence of frustrated phagocytosis or incomplete phagocytosis, as proposed by Poland et al 7) and Hubbs et al 24) , respectively.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations